Shifting Variants and Ideological Affiliations of Islamic Education Institutions in the Special Region of Yogyakarta - Machali, Imam; Safitri, Edi; Wulandari, Fitria (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study aimed to identify and map the development of the variants of Islamic Educational Institutions in Yogyakarta and analyze the map of the ideological affiliation of Islamic educational institutions. This type of research is field research. Data collection techniques are carried out using interviews, observation, and documentation. The data validity test used the source triangulation technique. The process of data analysis is data reduction, transcription, coding, grouping, comparing and contrasting, interpreting, and drawing conclusions. The results of the study indicate that Islamic Educational Institutions in Indonesia has developed and changed very rapidly. These changes and developments influence the variants and ideology of Islamic Educational Institutions in Yogyakarta. The shift in the variants of Islamic Educational Institutions in Yogyakarta can be mapped into four variants, i.e., the Religious Movement Variant, the Political Dakwah Variant, the Business Variant, and the Corporate Variant. Further, the ideological affiliations of Islamic educational institutions in Yogyakarta can be mapped into four, Compromising Ideology, Aswaja-Traditionalist, Modernist-Reformist, and Revivalist.